AML in Kazakhstan: Progress, Challenges and Future Prospects - Zhamiyeva, R.M.; Albekova, M.G. («Академик Е.А. Бөкетов атындағы Қарағанды университеті» КЕАҚ баспасы, 2023)
This academic article aims to analyze the current state and dynamics of developing the Anti-Money Laundering (AML) process in the Republic of Kazakhstan. The article reviews the regulatory framework for AML/CFT in Kazakhstan and discusses the government's efforts to combat money laundering in the country. The article also examines the role of financial institutions in implementing AML/CFT measures and the challenges faced by them. Based on the study and analysis of the national legislation of the Republic of Kazakhstan, the current problems of the formation and development of a system of counteraction to the legalization of criminal incomes are considered, and as a result, necessary measures will help to realize a necessary level of counteraction in the country. Also, the attention is focused on new money-laundering techniques such as using digital assets, which are actively used by criminal networks nowadays. In addition, the article highlights the recent developments and initiatives taken by Kazakhstan to strengthen its AML/CFT regime.
Қазақстандағы АЖ/ТҚҚ: прогресс, мәселелері және болашақ перспективалары
ПОД/ФТ в Казахстане: прогресс, проблемы и перспективы
Keywords: money laundering; criminal proceeds; financial monitoring; financial institutions; Financial Action Task Force (FATF); digital assets; Financial Monitoring Agency; financial operations